2014
DOI: 10.1364/oe.22.026076
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian design in readout from room-temperature Raman atomic memory

Abstract: We present an experimental demonstration of the Hamiltonian manipulation in light-atom interface in Raman-type warm rubidium-87 vapor atomic memory. By adjusting the detuning of the driving beam we varied the relative contributions of the Stokes and anti-Stokes scattering to the process of four-wave mixing which reads out a spatially multimode state of atomic memory. We measured the temporal evolution of the readout fields and the spatial intensity correlations between write-in and readout as a function of det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…There it was found that while fluorescence noise was negligible for off-resonant storage of short pulses, the thermal noise contributed by four-wave mixing destroyed the anti-bunching characteristic of single photons. Fourwave mixing noise is therefore the key roadblock preventing the implementation of Λ-memories at room temperature [27,28]. Suggested solutions to this problem include partial suppression via polarisation selection rules [29], and engineering a Raman absorption feature in an isotopically mixed vapour [30].…”
Section: Introductionmentioning
confidence: 99%
“…There it was found that while fluorescence noise was negligible for off-resonant storage of short pulses, the thermal noise contributed by four-wave mixing destroyed the anti-bunching characteristic of single photons. Fourwave mixing noise is therefore the key roadblock preventing the implementation of Λ-memories at room temperature [27,28]. Suggested solutions to this problem include partial suppression via polarisation selection rules [29], and engineering a Raman absorption feature in an isotopically mixed vapour [30].…”
Section: Introductionmentioning
confidence: 99%
“…Applications range from quantum optics, cold atomic physics and off-resonant light-atom interfaces [1][2][3][4][5], through frequency comb stabilization [6][7][8][9] to precision spectroscopy and sensing [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…
In multiple applications, phase coherence of the two laser fields locked at a frequency offset is not required [2][3][4][5][6][7][8][9][10][11] and a mere frequency lock is a sufficient solution. Nevertheless, one of the most commonly used solutions is the optical phase locked loop (OPLL) [12][13][14][15].
…”
mentioning
confidence: 99%
“…However, large control pulse energies are needed to drive the storage interaction far from resonance, and the control can also drive unwanted four-wave mixing, introducing noise which cannot be filtered out either spectrally or temporally. Four-wave mixing noise has emerged as the last remaining roadblock to the development of efficient Λ-type room-temperature quantum memories [17,[20][21][22][23]. We solve this problem by introducing a new cavity enhanced Raman memory protocol.…”
mentioning
confidence: 99%
“…However, unlike in single-atom cavity QED [31], where very high cavity quality factors are required to achieve the strong coupling regime and suppress spontaneous emission into any direction, here we require only the suppression of on-axis spontaneous anti-Stokes scattering, since off-axis scattering couples to momentum-orthogonal spin wave modes that are not phasematched [23] and do not contribute noise. Cavityenhanced ensemble Raman storage is therefore technically less demanding than cavity-QED-based storage, requiring only low-to moderate-finesse, which remains compatible with broadband operation (δ ∼ GHz).…”
mentioning
confidence: 99%